Health professional's readiness and factors associated with telemedicine implementation and use in selected health facilities in Ghana. Issue 3 (March 2023) - Mensah, Nathan Kumasenu; Adzakpah, Godwin; Kissi, Jonathan; Boadu, Richard Okyere; Lasim, Obed Uwumbornyi; Oyenike, Martha Khainde; Bart-Plange, Abigail; Dalaba, Maxwell Ayindenaba; Sukums, Felix
Abstract: Background: Telemedicine, which is the practice of medicine using technology to deliver health care remotely, has a low adoption rate in low- and middle-income countries (LMICs). However, the advent of coronavirus disease 2019 (COVID-19) has forced healthcare systems in these settings to begin implementing telemedicine programs. It is unknown how prepared health professionals and the healthcare system are to adopt this technology. Therefore, this study aimed to assess the readiness of health professionals and explore factors associated with telemedicine implementation in Ghana. Methods: A cross-sectional study was conducted in six health facilities between March and August 2021. Convenience sampling was used to select the six health facilities, and the participants were selected randomly for the study. Questionnaires were self-completed by participants. Data was exported into STATA 15.0 for analysis, and appropriate statistical methods were employed. All statistical tests were performed at a significance level of p < 0.05. Results: Of the 613 health professionals involved in the study, about 579 (94.5%) were comfortable using computers, and the majority, 503 (82.1%) of them, had access to computers at the workplace. Health professionals agreed that the measures outlined by the health facilities supported their readiness to use telemedicine for healthcare services. Analysis revealed a statistically significant positive relationship between health facilities' core readiness and health professionals' readiness, with a correlation coefficient (r) of 0.5484 and a p-value<0.0001. Of the factors associated with health professionals' readiness towards telemedicine implementation, facility core readiness, engagement readiness, staff knowledge and attitude readiness showed a statistically significant relationship with health professionals' readiness. Conclusion: The study revealed that health professionals are ready to adopt telemedicine. There was a statistically significant relationship between health facilities' core readiness, engagement readiness, staff knowledge and attitude readiness, and health professionals' readiness. The study identified factors facilitating telemedicine adoption.